Roadmap on multimode photonics. (1st August 2022) - Cristiani, Ilaria; Lacava, Cosimo; Rademacher, Georg; Puttnam, Benjamin J; Luìs, Ruben S; Antonelli, Cristian; Mecozzi, Antonio; Shtaif, Mark; Cozzolino, Daniele; Bacco, Davide; Oxenløwe, Leif K; Wang, Jian; et al.
Abstract: Multimode devices and components have attracted considerable attention in the last years, and different research topics and themes have emerged very recently. The multimodality can be seen as an additional degree of freedom in designing devices, thus allowing for the development of more complex and sophisticated components. The propagation of different modes can be used to increase the fiber optic capacity, but also to introduce novel intermodal interactions, as well as allowing for complex manipulation of optical modes for a variety of applications. In this roadmap we would like to give to the readers a comprehensive overview of the most recent developments in the field, presenting contributions coming from different research topics, including optical fiber technologies, integrated optics, basic physics and telecommunications.